Energy modelling and analysis of a multi-generation renewable energy system for dairy farm applications. Issue 3 (16th March 2021) - Cuomo, M. A.; Kool, E. D.; Reddy, B. V.; Rosen, M. A.
ABSTRACT: A multi-output energy-generation system for providing electricity and cooling for a grid-independent Ontario dairy farm is investigated. A range of biogas-fed micro turbines coupled with absorption refrigeration units and an organic Rankine cycle for heat recovery are considered to meet the electrical and cooling needs of farm sizes between 250 and 6000 cows. An energy analysis is conducted for the entire system and each subsystem. It is found that absorption refrigerators make best use of the energy in the exhaust stream, and increasing the amount of energy input to this subsystem increases overall system energy efficiency. Overall system energy efficiencies vary from 9 to 40%, increasing with farm size, while the energy efficiency of the bottoming cycle is 32–40% depending on farm size. For the range of configurations considered, electricity generation exceeds the farm's internal energy requirements, presenting opportunities for the sale of electricity.